Conserved RNA Binding Activity of Phosphatidyl Inositol 5-Phosphate 4-Kinase (PIP4K2A) - Behari, Jatin; Borkar, Pranita; Vindu, Arya; Dandewad, Vishal; Upadrasta, Sindhuri; Shanmugam, Dhanasekaran; Seshadri, Vasudevan (Frontiers in Molecular Biosciences, 2021)
Plasmodium falciparum is a causative agent for malaria and has a complex life cycle in human and mosquito hosts. During its life cycle, the malarial parasite Plasmodium goes through different asexual and sexual stages, in humans and mosquito. Expression of stage-specific proteins is important for successful completion of its life cycle and requires tight gene regulation. In case of Plasmodium, due to relative paucity of the transcription factors, it is postulated that post-transcriptional regulation plays an important role in stage-specific gene expression. Translation repression of specific set of mRNA has been reported in gametocyte stages of the parasite. A conserved element present in the 3’UTR of some of these transcripts was identified. Phosphatidyl-inositol 5-phosphate 4-kinase (PIP4K2A) was identified as the protein that associates with these RNAs. We now show that the RNA binding activity of the PIP4K2A is independent of its Kinase activity. We also observe that the PIP4K2A is imported into the parasite from host on Plasmodium berghei as well as Toxoplasma gondi. The RNA binding activity of PIP4K2A seems to be conserved across species from Drosophila, C. elegans to humans suggesting that RNA binding activity of PIP4K may be important and there may be host transcripts that may be regulated by PIP4K2A. These results identify a novel RNA binding role for PIP4K2A that may play a role not only in Plasmodium propagation but may also function in regulating gene expression in multicellular organism.